Correlation Between Neutrophil To Lymphocyte Ratio With Child Turcotte Pugh In Liver Cirrhosis Patients - Wiwiek Probowati; Putut Bayupurnama; Neneng Ratnasari (Faculty of Medicine Universitas Gadjah Mada, 2016)
Background: Neutrophil to lymphocyte ratio (NLR) is an index that iswidely used these days. RNL has been widely studied as a predictor of poor survival and outcome in patients with liver cirrhosis, hepatocellular carcinoma, coronary heart disease, rheumatoid arthritis, sepsis and malignancy.Objective: To determine whether there is a correlation between NLR with a score of Child turcotte pugh (CTP) in patients with liver cirrhosis in Dr. Sardjitogeneral Hospital.Methods :The study design was cross-sectional study. The study began in December 2014 until the number of samples are met. The subjects of this study were patients with liver cirrhosis at affordable populations undergoing inpatient and outpatient care in the Dr. Sardjito Hospital that meet the inclusion and exclusion criteria. Venous blood test to measure neutrophils,lymphocytes, albumin, total bilirubin, INR (Internationale normalized ratio). Data presented in the form of descriptive analysis of the characteristics of the study subjects such as the mean and standard deviation values of lymphocyte and neutrophil ratio scores CTP. For analyze the correlation between NLR with CTP scores Spearman nonparametric analysis p <0.05.Results : There are 33 subjects in the study. Based on the results of this study found a positive significant correlation between the ratio of neutrophils to lymphocytes CTP with r = 0.749 andp= <0.0001 and obtained the formula Y = 7.797 + 0,067x. Thus increasing of neutrophils to lymphocytes ratio positive correlated with the severity of liver cirrhosis.Conclusion. There are positive correlation between the neutrophil to lymphocyte ratio with CTP scores in patients with liver cirrhosis.